Studi Kualitatif Layanan Kesehatan Yang Diterima Orang Dengan HIV - Gusti Sumarsih; Mahathir Mahathir; Devia Putri Lenggogeni (Ners Jurnal Keperawatan, 2023)
Comprehensive health care service is right for people living with HIV / AIDS. It is important to know and dig deeply the need of healthcare services among people living with HIV as a vulnerable group. Exploration of health care provider services received by people living with HIV can provide a thick description related to the process of care and treatment. In-depth interviews conducted in nine people living with HIV who utilize health care services in Jakarta. In this phenomenological qualitative study researchers have used the data analysis stage according to Stevick-Colaizzi. This study identifies the essence of the health care received by people living with HIV are health care services information, easy access to health care services, service before the test, service after the test, get ARVs and treatment of health complaints. The findings recommend health care providers further optimized in order to give real impact in the prevention of HIV / AIDS pandemic.